Engineering globins for efficient biodegradation of malachite green: two case studies of myoglobin and neuroglobin. Issue 29 (24th June 2022) - Liu, Jiao; Xu, Jia-Kun; Yuan, Hong; Wang, Xiao-Juan; Gao, Shu-Qin; Wen, Ge-Bo; Tan, Xiang-Shi; Lin, Ying-Wu
Abstract : Engineered globins such as H64D Mb and A15C/H64D Ngb were efficient in the degradation of malachite green, with activities much higher than those of some native enzymes. Abstract : Malachite green (MG)-contaminated wastewater resulting from industrialization causes a global problem because of its toxicity and widespread usage. Compared with traditional physical and chemical approaches, biodegradation provides a new route for the degradation of MG. As promising candidates for native enzymes, artificial enzymes have received tremendous attention for potential applications due to unlimited possibilities based on precise design. In this study, we rationally engineered artificial enzymes based on myoglobin (Mb) and neuroglobin (Ngb). We introduced an aspartic acid (H64D mutation) in the heme pocket of Mb. A distal histidine (F43H mutation) was further introduced into H64D Mb to obtain a double mutant of F43H/H64D Mb. Moreover, we used A15C/H64D Ngb as designed recently for comparison studies. The H64D Mb, F43H/H64D Mb, and A15C/H64D Ngb were found to catalyze MG degradation efficiently, with activities much higher than those of native enzymes, such as dye-decolorizing peroxidase and laccase (83–205-fold). The crystal structure of H64D Mb was solved and the interactions of MG and H64D Mb and A15C/H64D Ngb were investigated by using both experimental and molecular docking studies. The biodegradation products of MG were also revealed by ESI-MS analysis. Therefore, these artificial enzymes have potential applications in the biodegradation of MG in textile industries and fisheries.